Sustainable Development: Enforcement of Environmental Criminal Law Against Illegal Logging Practices in Indonesia - Naila Nur Izzah (Peradaban Journal of Law and Society, 2022)
Every person in Indonesia has the right to have a good and healthy environment as a form of human rights; each generation has obligations and responsibilities in preserving the environment to ensure the welfare and quality of life between generations. Sustainable development is an effort to ensure these rights by managing natural resources wisely and rationally and paying attention to economic, social, and environmental aspects at the same time. Nowadays, humans tend to be greedy for current natural resources to get the most significant profit. Illegal Logging is an activity of placing forest resources on a large scale without paying attention to the needs of future generations. The research method used is normative (library study) by emphasizing research sourced from the literature. The results of this study indicate that the efforts made by the government in realizing the concept of sustainable development as is Law Number 32 of 2009 is about Environmental Protection and Management, and Law Number 18 of 2013 is about Prevention and Eradication of Forest Destruction as a form of preventive and repressive efforts to the environment. The environment is related to humans; therefore, all society must be aware of protecting and preserving environmental ecosystems.